Imagining New England : explorations of regional identity from the pilgrims to the mid-twentieth century - Conforti, Joseph A. (University of North Carolina Press, 2001)
An investigation of New England as a cultural invention, tracing the region's changing identity across more than three centuries. It incorporates insights from history, literature, art, culture and geography to show how generations of New Englanders created a powerful collective identity.